Psychometric evaluation of the nine-item heart failure self-care behavior scale (9-EHFScBS) - Reza Negarandeh; Elham Ghasemi; Leila Janani (Tehran University of Medical Sciences, 2021)
Background & Aim: Self-care in patients with heart failure can improve multiple outcomes and reduce mortality. Measuring self-care requires valid and reliable tools. This study aimed to determine the psychometric properties of the 9-items European Heart Failure Self-Care Behavior Scale. Methods & Materials: The present study is a psychometric evaluation. The original version of the tool was translated from English to Persian using the standard Backward-Forward method. The questionnaire's validity was assessed using face, content, criterion (the Self-Care of Heart Failure Index v.6 as a criterion), and construct validity.  An exploratory factor analysis approach was used to construct validity with a sample of 216 patients with chronic heart failure referred to Dr. Shariati and Imam Khomeini Hospital's heart clinics in Tehran; and Ayatollah Mousavi Hospital in Zanjan. The reliability of the questionnaire was evaluated by internal consistency and stability methods. Results: After the validation process (validity and reliability), all 9 items of the questionnaire were approved and remained. The content validity index of the total content of the questionnaire was calculated to be 0.96. Based on factor analysis, only one factor was confirmed for the questionnaire. The correlation between the present questionnaire and the Self-Care of Heart Failure Index v.6 was positive and significant (p<0.001, r=0.753). Internal consistency (α=0.728) and stability (0.897) of the questionnaire were also confirmed. Conclusion: The European Heart Failure Self-Care Behavior Scale is valid and reliable for measuring Iranian patients' self-care behaviors with heart failure.